Application of combined U-Th-disequilibrium/U-Pb and (U-Th)/He zircon dating to tephrochronology - Danišik, Martin; Schmitt, Axel Karl (Quaternary geochronology, 2017)
The combination of U-Th disequilibrium/U-Pb and (U-Th)/He dating of zircon (ZDD) has provided a relatively new radiometric approach suitable for dating Quaternary zircon-bearing volcanic and pyroclastic deposits. This approach permits the dating of zircon as young as ca. 2.5 ka and has huge potential for tephrochronology and other ﬁelds of Quaternary science. Its applicability range covers the critical time-window in Quaternary geochronology beyond the range of 14C and below the limit of routine Ar/Ar dating (i.e. between ca. 50 ka and 1.5 Ma). The combined U-Th disequilibrium/U-Pb and (U-Th)/He dating approach can also be applied to other actinide-rich minerals such as allanite or monazite. In <1 Ma young volcanic samples, the integration of the low-temperature (U-Th)/He geochronometer with the hightemperature U-Th disequilibrium/U-Pb geochronometers is essential in order to correct for disequilibrium in the U-decay chains which, when ignored, may result in erroneous underestimation of true eruption ages.